Lubrication basics - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
This interactive training unit is designed to familiarize trainees with the properties and uses of various types of lubricants. After completing this unit, trainees should be able to explain why lubricants are used and describe some characteristic properties of lubricants. They should also be able to describe procedures for storing, handling, and applying lubricants.
Keywords: Lubrication and lubricants